A study on the longitudinal compression strength of fibre reinforced composites under uniaxial and off-axis loads using cross-ply laminate specimens. - Thomson, Daniel; Cui, Hao; Erice, Borja; Petrinic, Nik (Elsevier, 2019)
Abstract Longitudinal compression testing of unidirectional FRP laminates remains a challenge due to the difficulty in applying high compressive loads without stress concentrations and boundary effects leading to premature failure. This work aims to critically evaluate different specimen designs and laminate configurations, cross-ply in particular, for the determination of longitudinal compression properties of unidirectional plies. To this end, a comprehensive experimental campaign has been carried out, comparing strength, stiffness, and failure modes across different specimen designs and laminate configurations. The investigated cross-ply specimens produced comparable results without many of the issues observed in the testing unidirectional material and, therefore, are strongly recommended for the determination of longitudinal compressive strength. Finally, the cross-ply material was tested under off-axis compression to study the effects of shear on the longitudinal compression strength using a series of compression specimens cut at different angles between 0 and 15° to the direction of the laminate.
Keywords: Polymer matrix composites; Mechanical properties; Longitudinal compression; Buckling